2019
DOI: 10.1177/0146167219873480
|View full text |Cite
|
Sign up to set email alerts
|

Your Soul Spills Out: The Creative Act Feels Self-Disclosing

Abstract: Breaking from the typical focus on the antecedents of creativity, we investigate the psychological and interpersonal consequences of being creative. Across five experiments, we find that generating creative ideas is revealing of the self and thus prompts the perception of self-disclosure. Individuals respond to the expectation to be creative with greater self-focus—adopting their own idiosyncratic perspective on the task and thinking about their own personal preferences and experiences in connection to the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Only if ideas have an independent existence can they be owned by an individual who is not their creator. This is the premise of studies on the psychological experiences of ownership, which have shown how generating ideas is experienced as disclosing information about or aspects of oneself (Goncalo & Katz, 2019), that psychological ownership affects how people adopt others' suggestions for change (Baer & Brown, 2012), and the extent to which they elaborate information (Knight & Baer, 2014). Similarly, the premise of research on idea management (Vandenbosch, Saatcioglu, & Fay, 2006) is that ideas can be treated like a collection of objects (e.g., Litchfield & Gilson, 2013).…”
Section: The Location Of Ideasmentioning
confidence: 99%
“…Only if ideas have an independent existence can they be owned by an individual who is not their creator. This is the premise of studies on the psychological experiences of ownership, which have shown how generating ideas is experienced as disclosing information about or aspects of oneself (Goncalo & Katz, 2019), that psychological ownership affects how people adopt others' suggestions for change (Baer & Brown, 2012), and the extent to which they elaborate information (Knight & Baer, 2014). Similarly, the premise of research on idea management (Vandenbosch, Saatcioglu, & Fay, 2006) is that ideas can be treated like a collection of objects (e.g., Litchfield & Gilson, 2013).…”
Section: The Location Of Ideasmentioning
confidence: 99%
“…Following the power prime, participants were introduced to a creative task, which was to generate novel ideas for a new candle scent following procedures used in previous research (Goncalo & Katz, 2020). Specifically, the participants read the following: "This next section is a task about product development.…”
Section: Methodsmentioning
confidence: 99%
“…Idea novelty. Two independent coders scored the novelty of participants' candle scent ideas, following Goncalo and Katz (2020). Specifically, two trained coders who were blind to the experimental condition and predictions of the study coded each idea for novelty, which was defined as "the extent to which the idea does not resemble the typical candle scent".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Creative workers often forge strong links between their self-concept and what they create (e.g., Elsbach & Flynn, 2013;Rouse, 2016;Baer & Brown, 2012). Jazz musicians are no differentthey view their playing as reflections of themselves (Goncalo & Katz, 2019).…”
Section: Using a "Third Ear": Creating A Passive Observer Role For Conscious Intentionmentioning
confidence: 99%